Toner for developing electrostatic images

The use of lanthanum-containing strontium titanate particles in toner base particles with a binder resin and metal pigment uniformizes charging characteristics, preventing scattering and ensuring high-quality images with metallic luster.

JP7615675B2Active Publication Date: 2025-01-17KONICA MINOLTA INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2020218791
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-28
Publication Date
2025-01-17
Estimated Expiration
2040-12-28

AI Technical Summary

Technical Problem

The charging characteristics of glitter toners containing metal pigments are uneven, leading to non-uniform charge distribution and scattering during continuous printing, which affects image quality and environmental safety.

Method used

A toner formulation comprising toner base particles with a binder resin and metal pigment, combined with an external additive of lanthanum-containing strontium titanate particles, which uniformizes charging characteristics by filling recesses on the toner surface and enhances adhesion.

Benefits of technology

The toner effectively suppresses scattering during continuous printing, ensuring high-quality images with metallic luster and reducing environmental contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615675000001
    Figure 0007615675000001
Patent Text Reader

Abstract

To provide electrostatic charge image developing toner that includes a metallic pigment, and can suppress occurrence of toner scattering even upon continuous printing.SOLUTION: Electrostatic charge image developing toner comprises: a toner mother particle that contains a binder resin and a metallic pigment; and an external additive that contains a lanthanum-containing strontium titanate particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner for developing electrostatic images. [Background technology]

[0002] In recent years, the use of electrophotographic image forming apparatuses has become more diverse with the widespread use of such apparatuses. In some cases, the image forming apparatuses are required to output high-value-added images, such as those seen in the commercial printing field, and are also required to form images with metallic luster. Images with metallic luster are usually formed using a glossy toner.

[0003] The glittering toner contains, in addition to a binder resin, a metal pigment made of a powder of a metal such as aluminum, brass, bronze, nickel, stainless steel, or zinc (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-62315 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the glitter toner containing the binder resin and the metal pigment as described above, the charging characteristics of the binder resin and the metal pigment are significantly different. In other words, the charging characteristics are significantly different between the area where the metal pigment is present and the area where it is not present. Therefore, the charging characteristics on the toner surface are easily non-uniform. If the charging characteristics on the toner surface are non-uniform, the charge distribution of the toner becomes wider during continuous printing. Furthermore, there is a problem that the glitter toner with a low charge amount is easily dropped off from the photosensitive layer of the image forming device and easily scattered into the atmosphere.

[0006] The present invention has been made in view of the above problems, and specifically, an object of the present invention is to provide a toner for developing electrostatic images, which contains a metal pigment and can suppress the occurrence of toner scattering even during continuous printing. [Means for solving the problem]

[0007] The present invention provides the following toner for developing electrostatic images. A toner for developing electrostatic images, comprising toner base particles containing a binder resin and a metal pigment, and an external additive containing lanthanum-containing strontium titanate particles. Effect of the Invention

[0008] According to the toner for developing electrostatic images of the present invention, the toner for developing electrostatic images is unlikely to scatter even during continuous printing, and furthermore, it is possible to form high-value-added images having metallic luster. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] An embodiment of the present invention will be described in detail below, although the present invention is not limited to this embodiment.

[0010] As described above, conventional glitter toners containing metal pigments tend to have uneven charging characteristics on the surface of the glitter toner, and the glitter toner is prone to scattering during continuous printing. When the glitter toner scatters, not only does it have an adverse effect on the environment, but it also causes the glitter toner to adhere to areas other than the desired area, making it difficult to obtain high-quality images.

[0011] The present inventors have conducted extensive research into this issue and have found that a toner for developing electrostatic images (hereinafter, also simply referred to as "toner") that contains toner base particles that contain a binder resin and a metal pigment, and an external additive that contains lanthanum-containing strontium titanate particles, is less likely to scatter even when continuous printing is performed. The reasons for this are considered to be as follows.

[0012] The surface of the toner base particle containing the binder resin and the metal pigment is uneven, and usually the part containing the metal pigment is the convex part, and the part not containing the metal pigment is the concave part. On the other hand, the lanthanum-containing strontium titanate has a structure close to a sphere, and when mixed with the base particle having the above-mentioned unevenness, it enters into the concave part of the surface of the toner base particle. In addition, the lanthanum-containing strontium titanate particles have a charging characteristic similar to that of the above-mentioned metal pigment. Therefore, when the lanthanum-containing strontium titanate particles enter into the concave part of the surface of the toner base particle, the charging characteristic of the toner surface becomes uniform.

[0013] In addition, lanthanum-containing strontium titanate has a relatively large specific gravity, and when mixed with toner base particles, a part of it penetrates into the toner base particles and is relatively firmly fixed therein. Therefore, even when continuous printing is performed or stress is applied in a developing device, lanthanum-containing strontium titanate is unlikely to move or become detached from the surface of the toner base particles, and the effect can be fully exerted.

[0014] Here, the toner of the present invention may contain at least the toner base particles and the external additive, but may contain other components within a range that does not impair the object and effect of the present invention. The toner of the present invention may be a one-component developer or a two-component developer. When the toner is a two-component developer, it further contains carrier particles in addition to the toner base particles and the external additive (hereinafter, these are also collectively referred to as "toner particles"). Each component will be described in detail below.

[0015] (1) Toner base particles The toner base particles contain at least a binder resin and a metal pigment, and may further contain a release agent, etc., as necessary.

[0016] (Binding resin) The binder resin is a resin that functions to bind the toner particles to a recording medium, and preferably contains an amorphous resin and a crystalline resin.

[0017] The content of the binder resin is preferably 50 to 95% by mass, more preferably 70 to 90% by mass, based on the total amount of the toner base particles. When the amount of the binder resin is within this range, an image formed using the toner is easily fixed to a recording medium.

[0018] Amorphous resin The amorphous resin contained in the binder resin may be a resin that does not substantially have crystallinity. In this specification, "not substantially exhibiting crystallinity" means that the resin does not have a melting point when subjected to differential scanning calorimetry (DSC).

[0019] Examples of the amorphous resin include vinyl resin, urethane resin, urea resin, amorphous polyester resin, etc. Among these, vinyl resin is preferred because it is less susceptible to environmental variations. The binder resin may contain only one type of amorphous resin, or may contain two or more types.

[0020] The vinyl resin is not particularly limited as long as it is a polymer of a vinyl compound, and examples thereof include (meth)acrylic acid ester resin, styrene-(meth)acrylic acid ester resin, ethylene-vinyl acetate resin, etc. Among these, styrene-(meth)acrylic acid ester resin is more preferable in consideration of plasticity during thermal fixing. In this specification, (meth)acrylic means methacrylic, acrylic, and a mixture thereof.

[0021] A preferred styrene-(meth)acrylic acid ester resin (hereinafter also referred to as "styrene-(meth)acrylic resin") will be described below.

[0022] Styrene-(meth)acrylic resin is a resin obtained by addition polymerization of at least a styrene-based monomer and a (meth)acrylic acid ester monomer. In this specification, the styrene-based monomer includes not only styrene represented by the structural formula CH2=CH-C6H5, but also compounds in which any side chain or functional group is bonded to the styrene skeleton. In addition, in this specification, the (meth)acrylic acid ester monomer includes not only acrylic acid ester compounds and methacrylic acid ester compounds represented by CH2=CHCOOR (R is an alkyl group), but also ester compounds in which any side chain or functional group is bonded, such as acrylic acid ester derivatives and methacrylic acid ester derivatives.

[0023] Specific examples of the styrene monomer include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, etc. The styrene-(meth)acrylic resin may contain only one type of structure derived from these, or may contain two or more types.

[0024] On the other hand, specific examples of (meth)acrylic acid ester monomers include acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, lauryl acrylate, and phenyl acrylate; and methacrylic acid ester monomers such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, phenyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminoethyl methacrylate. The styrene-(meth)acrylic resin may contain only one type of structure derived from these, or may contain two or more types.

[0025] The content of structural units derived from styrene-based monomers in the styrene-(meth)acrylic resin is preferably 40 to 90% by mass. The content of structural units derived from (meth)acrylic acid ester monomers in the styrene-(meth)acrylic resin is preferably 10 to 60% by mass. The styrene-(meth)acrylic resin may contain structures derived from other monomers in addition to the structures derived from the above styrene-based monomers and (meth)acrylic acid ester monomers.

[0026] Examples of other monomers include compounds having a carboxyl group such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, cinnamic acid, fumaric acid, maleic acid monoalkyl ester, and itaconic acid monoalkyl ester; and compounds having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. The styrene-(meth)acrylic resin may contain only one type of structure derived from these, or may contain two or more types.

[0027] However, the content of structural units derived from other monomers in the styrene-(meth)acrylic resin is preferably 0.5 to 20% by mass.

[0028] The weight average molecular weight (Mw) of the styrene-(meth)acrylic resin is preferably 10,000 to 100,000. When the weight average molecular weight of the styrene-(meth)acrylic resin is within this range, the strength of the obtained image is increased.

[0029] The method for producing the styrene-(meth)acrylic resin is not particularly limited. A styrene monomer, a (meth)acrylic acid ester monomer, and other monomers, if necessary, may be polymerized by a known polymerization method such as bulk polymerization, solution polymerization, emulsion polymerization, miniemulsion polymerization, or dispersion polymerization using any polymerization initiator such as a general peroxide, persulfide, persulfate, or azo compound. A general chain transfer agent may be used to adjust the molecular weight. The chain transfer agent is not particularly limited, and examples thereof include alkyl mercaptans such as n-octyl mercaptan, mercapto fatty acid esters, and the like.

[0030] In addition, when producing a styrene-(meth)acrylic resin, the polymerization may be carried out in multiple stages. For example, by carrying out the polymerization in multiple stages while changing the types and ratios of the styrene-based monomer and the (meth)acrylic acid ester monomer, it becomes possible to adjust the physical properties of the amorphous resin to a desired range.

[0031] The glass transition temperature (Tg) of the styrene / (meth)acrylic resin is not particularly limited, but is preferably 25 to 60° C. in order to reliably obtain fixability such as low-temperature fixability, heat-resistant storage stability, and heat resistance such as blocking resistance.

[0032] In order to increase the mechanical strength of the toner base particles and suppress embedding of the lanthanum-containing strontium titanate particles, the amorphous resin may contain an amorphous polyester resin in addition to the styrene-(meth)acrylic resin.

[0033] The amorphous polyester resin is a resin obtained by polycondensation of a polyvalent carboxylic acid or its derivative with a polyhydric alcohol or its derivative. During the polycondensation, a catalyst may be used as necessary.

[0034] Examples of polycarboxylic acids include oxalic acid, succinic acid, maleic acid, adipic acid, β-methyladipic acid, azelaic acid, sebacic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, fumaric acid, citraconic acid, diglycolic acid, cyclohexane-3,5-diene-1,2-dicarboxylic acid, malic acid, citric acid, hexahydroterephthalic acid, malonic acid, pimelic acid, tartaric acid, mucic acid, phthalic acid, isophthalic acid, terephthalic acid, tetrachlorophthalic acid, chlorophthalic acid, nitrophthalic acid, p-carboxyphenylacetic acid, p-phenylene diacetic acid, m-phenylene diacetic acid, and m-phenylene diacetic acid. These include divalent carboxylic acids such as ethylene diglycolic acid, p-phenylenediglycolic acid, o-phenylenediglycolic acid, diphenylacetic acid, diphenyl-p,p'-dicarboxylic acid, naphthalene-1,4-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, naphthalene-2,6-dicarboxylic acid, anthracene dicarboxylic acid, and dodecenyl succinic acid; trivalent or higher carboxylic acids such as trimellitic acid, pyromellitic acid, naphthalene tricarboxylic acid, naphthalene tetracarboxylic acid, pyrene tricarboxylic acid, and pyrene tetracarboxylic acid; alkyl esters thereof; acid anhydrides thereof; and acid chlorides thereof. The amorphous polyester resin may contain only one type of structure derived from these, or may contain two or more types. Among the above, unsaturated aliphatic dicarboxylic acids such as fumaric acid, maleic acid, and mesaconic acid are preferred.

[0035] On the other hand, examples of polyhydric alcohols include dihydric alcohols such as ethylene glycol, propylene glycol, butanediol, diethylene glycol, hexanediol, cyclohexanediol, octanediol, decanediol, dodecanediol, an ethylene oxide adduct of bisphenol A, and a propylene oxide adduct of bisphenol A; trivalent or higher polyols such as glycerin, pentaerythritol, hexamethylolmelamine, hexaethylolmelamine, tetramethylolbenzoguanamine, and tetraethylolbenzoguanamine; ester compounds thereof; and hydroxycarboxylic acids thereof. The amorphous polyester resin may contain only one type of structure derived from these, or may contain two or more types.

[0036] Here, the total amount of the amorphous resin relative to the total amount of the binder resin is preferably 5 to 30% by mass. When the amount of the amorphous polyester is 5% by mass or more, the strength of the obtained image is likely to be increased. On the other hand, when the amount of the amorphous resin is 30% by mass or less, the amount of the crystalline resin tends to be relatively sufficient, and the fixing property at low temperatures tends to be good.

[0037] Crystalline resin When the binder resin contains a crystalline resin, the flexibility of the toner base particles is likely to increase, and the lanthanum-containing strontium titanate particles are likely to adhere to the periphery of the toner base particles. In this specification, "crystalline" means that there is a clear endothermic peak, not a stepwise endothermic change, in differential scanning calorimetry (DSC). A "clear endothermic peak" means a peak whose half-width of the endothermic peak is within 15°C when measured in DSC at a heating rate of 10°C / min. The smaller the half-width of the endothermic peak, the higher the degree of crystallinity.

[0038] Here, the type of the crystalline resin is not particularly limited, but a crystalline polyester resin is particularly preferred. When the binder resin contains a crystalline polyester resin, the toner base particles are easily melted by heating, and low-temperature fixability is improved.

[0039] The crystalline polyester resin is, for example, a resin obtained by a polycondensation reaction between the following polyvalent carboxylic acid and the following polyhydric alcohol.

[0040] Examples of polyvalent carboxylic acids include saturated aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, n-dodecyl succinic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, and tetradecanediol; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; trivalent or higher polyvalent carboxylic acids such as trimellitic acid and pyromellitic acid; anhydrides thereof; and alkyl (carbon number 1 to 3) esters thereof. The crystalline polyester resin may contain only one type of structure derived from these, or may contain two or more types.

[0041] Examples of polyhydric alcohols include aliphatic diols such as 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, dodecanediol, neopentyl glycol, and 1,4-butenediol; and trihydric or higher polyhydric alcohols such as glycerin, pentaerythritol, trimethylolpropane, and sorbitol. The crystalline polyester resin may contain only one type of structure derived from these, or may contain two or more types.

[0042] The total amount of the crystalline polyester in the binder resin is preferably 5 to 20% by mass based on the total amount of the binder resin. When the amount of the crystalline polyester is 5% by mass or more, low-temperature fixability is easily obtained. Also, when the amount of the crystalline polyester is 20% by mass or less, the toner is easily prepared.

[0043] The melting point of the crystalline polyester resin in this specification is preferably 60 to 90°C. The melting point of the crystalline polyester resin is measured as follows. First, 3.0 g of a sample is sealed in an aluminum pan, and a differential scanning calorimeter (for example, Diamond DSC, manufactured by PerkinElmer) is used to raise the temperature from 0°C to 200°C at a heating rate of 10°C / min (first heating process). Next, the sample is cooled from 200°C to 0°C at a cooling rate of 10°C / min (cooling process). Then, the sample is heated from 0°C to 200°C at a heating rate of 10°C / min (second heating process). Then, a DSC curve is prepared from these measurement results, and the endothermic peak top temperature derived from the crystalline polyester resin in the first heating process is taken as the melting point (Tm). An empty aluminum pan is used as a reference.

[0044] Hybrid resin The binder resin may further contain a resin (hybrid resin) having a vinyl-based segment and a polyester-based segment. In the hybrid resin, the vinyl-based segment and the polyester-based segment are preferably bonded via a structure derived from a bireactive monomer. When the binder resin contains a hybrid resin, the dispersibility of the crystalline resin in the amorphous resin becomes better.

[0045] The vinyl-based segment in the hybrid resin is composed of a vinyl resin. Here, the vinyl resin is the same as that described above for the amorphous resin. The amount of the vinyl-based segment in the hybrid resin is preferably 0.5 to 20% by mass based on the total amount of segments.

[0046] On the other hand, the polyester-based segment in the hybrid resin is preferably composed of a crystalline polyester resin obtained by polycondensation reaction of a polycarboxylic acid and a polyhydric alcohol in the presence of a catalyst. The polycarboxylic acid and the polyhydric alcohol are the same as those described above for the crystalline resin. The amount of the polyester-based segment in the hybrid resin is preferably 0.5 to 20% by mass based on the total amount of segments.

[0047] The bireactive monomer is a monomer capable of reacting with both the crystalline polyester resin and the vinyl resin. The bireactive monomer preferably has, in the molecule, a group selected from the group consisting of a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group, and a secondary amino group, which reacts with the crystalline polyester resin (polyester-based segment), and an ethylenically unsaturated group which reacts with the vinyl resin (vinyl-based segment). As the bireactive monomer, a monomer having a hydroxyl group or a carboxyl group and an ethylenically unsaturated group is more preferable, and a monomer having a carboxyl group and an ethylenically unsaturated group is even more preferable. That is, the bireactive monomer is preferably a vinyl-based carboxylic acid.

[0048] Specific examples of the dual-reactive monomer include acrylic acid, methacrylic acid, fumaric acid, maleic acid, and their hydroxyalkyl (having 1 to 3 carbon atoms) esters. From the viewpoint of reactivity, the dual-reactive monomer is preferably acrylic acid, methacrylic acid, or fumaric acid.

[0049] The amount of the constitutional unit derived from the bireactive monomer in the hybrid resin is preferably 1 to 10 parts by mass, more preferably 4 to 8 parts by mass, per 100 parts by mass of the vinyl-based segment, from the viewpoint of improving the low-temperature fixing property, high-temperature offset resistance and durability of the toner.

[0050] The method for preparing the hybrid resin is not particularly limited, and the hybrid resin can be prepared by a known method. Representative methods include the following three methods.

[0051] (1) A method in which a polyester-based segment is polymerized in advance, a bireactive monomer is reacted with the polyester-based segment, and a monomer for forming a vinyl-based segment is further reacted with the polyester-based segment.

[0052] (2) A method in which a vinyl-based segment is polymerized in advance, the vinyl-based segment is reacted with a bireactive monomer, and further reacted with a polyvalent carboxylic acid and a polyhydric alcohol to form a polyester-based segment.

[0053] (3) A method in which a polyester segment and a vinyl segment are prepared separately, and then reacted with a bireactive monomer to bond the two.

[0054] Any of the above methods may be used, but the above method (2) is preferred. Specifically, a polyvalent carboxylic acid and a polyhydric alcohol forming a polyester-based segment, and a vinyl resin and a bireactive monomer forming a vinyl-based segment are mixed, and a polymerization initiator is added to perform addition polymerization of the vinyl-based segment resin and the bireactive monomer. Then, an esterification catalyst is added to bond the polyester-based segments.

[0055] The catalyst for synthesizing the polyester polymerization segment may be a known catalyst, examples of which include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, titanium compounds such as titanium diisopropylate bistriethanolamine, etc. Examples of the esterification promoter include gallic acid, etc.

[0056] (Metal Pigments) The metallic pigment is not particularly limited as long as it contains a metal and can impart metallic luster to an image. For example, it may be a metal powder such as aluminum, brass, bronze, nickel, stainless steel, zinc, copper, silver, gold, platinum, or a flaky glass powder on which metal is deposited. The metallic pigment may contain only one of these, or may contain two or more of them. Among these, aluminum is preferred from the viewpoint of availability. The surface of the metallic pigment may be coated with silica particles, acrylic resin, polyester resin, or the like.

[0057] The shape of the metal pigment is not particularly limited, and may be spherical, scaly, or flat.

[0058] The particle size of the metallic pigment is preferably 100 to 1000 nm, more preferably 150 to 500 nm, in terms of the volume-based median diameter. When the average particle size of the metallic pigment is within this range, an image having metallic luster is easily obtained. On the other hand, when the average particle size of the metallic pigment is within this range, the problems of the present invention are easily caused.

[0059] The content of the metallic pigment is preferably 1 to 70% by mass, more preferably 5 to 50% by mass, based on the total amount of the toner base particles. When the amount of the metallic pigment is within this range, a high-quality image is easily obtained when the image is formed using the toner.

[0060] (Release agent) The toner base particles may further contain a release agent, which is a component that seeps out from the toner particles during development and enhances fixing and releasability.

[0061] Wax is usually used as the release agent. Specific examples of the release agent include polyolefin waxes such as polyethylene wax and polypropylene wax; Fischer-Tropsch wax; branched chain hydrocarbon waxes such as microcrystalline wax; long chain hydrocarbon waxes such as paraffin wax and Sasol wax; dialkyl ketone waxes such as distearyl ketone; ester waxes such as carnauba wax, montan wax, behenic acid behenate, trimethylolpropane tribehenate, pentaerythritol tetrabehenate, pentaerythritol diacetate dibehenate, glycerin tribehenate, 1,18-octadecanediol distearate, trimellitic acid tristearyl, and distearyl maleate; amide waxes such as ethylenediamine behenylamide and trimellitic acid tristearylamide; and the like. The toner base particles may contain only one of these release agents, or may contain two or more of them.

[0062] The content of the releasing agent is preferably 2 to 30% by mass based on the total amount of the toner base particles. When the amount of the releasing agent is within this range, the fixing and releasability tends to be good.

[0063] (others) The toner base particles may further contain other components in addition to the binder resin, the metal pigment, and the release agent described above. Examples of the other components include colorants other than the metal pigment, charge control agents, etc.

[0064] Examples of colorants include carbon black, magnetic materials, pigments, dyes, etc. The toner base particles may contain only one type of colorant, or may contain two or more types of colorants. The amount of colorant is appropriately selected according to the desired color, type of colorant, etc.

[0065] On the other hand, the charge control agent is not particularly limited as long as it is a substance that can give a positive or negative charge by frictional charging, and various known positive charge control agents and negative charge control agents can be used. Examples of the charge control agent include nigrosine dyes, metal salts of naphthenic acid or higher fatty acids, alkoxylated amines, quaternary ammonium salt compounds, azo metal complexes, and salicylic acid metal salts or metal complexes thereof. The toner base particles may contain only one type of charge control agent, or may contain two or more types. The amount of the charge control agent is preferably 2 to 20 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the total amount of the binder resin.

[0066] (Structure of toner base particles) The structure of the toner base particle may be a single layer structure, or a multi-layer structure such as a core-shell structure having a core and a shell layer covering the surface of the core. The shell layer does not have to cover the entire surface of the core, and the core may be partially exposed. The cross section of the core-shell structure can be confirmed by known observation means such as a transmission electron microscope (TEM) or a scanning probe microscope (SPM). The core-shell structure in this specification also includes a triple or more layer structure.

[0067] When the toner base particle has a core-shell structure, the core and the shell layer can have different properties such as glass transition point, melting point, and hardness. Therefore, the toner base particle can have physical properties according to the purpose. For example, the shell layer can be formed by aggregating and fusing a resin with a relatively high glass transition point to the surface of a core with a relatively low glass transition point, which contains a binder resin, a metal pigment, a release agent, etc.

[0068] The average circularity of the toner base particles is preferably 0.920 to 0.100. When the circularity of the toner base particles is within this range, the contact points between the toner particles are small. This improves the external force responsiveness and increases the fluidity. As a result, a toner with excellent toner replenishment properties is obtained. When the average circularity is within this range, the transfer efficiency is also good. The average circularity can be measured using a flow type particle image analyzer (e.g., FPIA-3000, manufactured by Sysmex Corporation) or the like.

[0069] Specifically, the toner base particles are wetted with an aqueous surfactant solution and ultrasonically dispersed for 1 minute. After dispersion, the flow type particle image analyzer is used to perform measurement under the measurement conditions of HPF (high magnification imaging) mode at an appropriate concentration of 3,000 to 10,000 HPF detections. The circularity is calculated by the following formula. The average circularity is the arithmetic mean value obtained by adding up the circularities of the toner base particles and dividing the total number of particles measured. Circularity = (perimeter of a circle with the same projected area as the particle image) / (perimeter of the projected particle image)

[0070] The volume average particle diameter of the toner base particles is preferably 4.5 to 8.0 μm in terms of volume-based median diameter (D50). From the viewpoint of improving image quality, a smaller diameter is preferable, but a smaller particle diameter tends to increase the adhesion of the toner base particles and decrease the degree of fluidization. In contrast, if the volume average particle diameter of the toner base particles is within the above range, it is possible to achieve both the image quality of the output image and the toner supply property, and charging, development, transfer, cleaning, etc. can also be performed well. The volume average particle diameter of the toner base particles is more preferably 5.0 to 6.2 μm. If the volume average particle diameter is within this range, dot reproducibility is also improved, and images of higher image quality can be obtained.

[0071] The volume-based median diameter (D50) of the toner base particles can be measured and calculated using a particle size distribution measuring device (e.g., Multisizer 3, manufactured by Beckman Coulter, Inc.) connected to a computer system for data processing (e.g., Software V3.51, manufactured by Beckman Coulter, Inc.).

[0072] More specifically, 0.02 g of toner base particles are mixed with 20 ml of surfactant aqueous solution, and then ultrasonic dispersion is performed for 1 minute to prepare a toner base particle dispersion. An example of a surfactant aqueous solution is a solution in which a neutral detergent containing a surfactant component is diluted 10 times with pure water. This toner base particle dispersion is dropped into an electrolyte ISOTON II (manufactured by Beckman Coulter) until the measurement concentration is 5 to 10%, and the measurement is performed by setting the measurement count to 25,000 particles. Here, the aperture diameter of the particle size distribution measurement device is 100 μm. The measurement is performed by dividing the range of 2 to 60 μm into 256 parts and calculating the frequency, and the particle size of the largest 50% of the volume cumulative fraction is taken as the volume-based median diameter (D50).

[0073] (Method of Preparing Toner Base Particles) Although the method for preparing the toner base particles is not particularly limited, it is preferable to prepare the toner base particles by an emulsion aggregation method, which can obtain toner base particles having a sharp particle size distribution and a highly controlled particle size.

[0074] When preparing toner base particles by the emulsion aggregation method, the toner base particles can be prepared by the following procedure. First, a metal pigment dispersion liquid is prepared in which a metal pigment is dispersed in an aqueous medium. Meanwhile, a binder resin dispersion liquid is also prepared in which binder resin particles are dispersed in an aqueous medium. The metal pigment dispersion liquid and the binder resin dispersion liquid are then mixed to aggregate, associate, and fuse the metal pigment and the binder resin particles to form toner base particles. The toner base particles are then filtered and dried.

[0075] When aggregating the metal pigment and the binder resin fine particles, a flocculant may be used. Examples of the flocculant include metal salts, and specific examples include monovalent metal salts such as alkali metal salts such as sodium, potassium, and lithium; divalent metal salts such as calcium, magnesium, manganese, and copper; and trivalent metal salts such as iron and aluminum. More specific examples include sodium chloride, potassium chloride, lithium chloride, calcium chloride, magnesium chloride, zinc chloride, copper sulfate, magnesium sulfate, and manganese sulfate. These may be used alone or in combination of two or more. Among these, divalent metal salts are particularly preferred. When a divalent metal salt is used, a small amount can be used to aggregate the metal pigment and the binder resin fine particles.

[0076] (2) External additives The external additive is a component that serves to control the fluidity, charging characteristics, etc. of the toner particles. The external additive may contain at least lanthanum-containing strontium titanate particles, but may further contain other particles.

[0077] (Lanthanum-containing strontium titanate particles) Lanthanum-containing strontium titanate is a compound obtained by doping strontium titanate with lanthanum, which is highly reactive and difficult to grow as a crystal. The amount of lanthanum atoms in the lanthanum-containing strontium titanate particles is preferably 3 to 12% by mass, more preferably 5 to 10% by mass. The greater the amount of lanthanum in the lanthanum-containing strontium titanate particles, the easier it is for the shape of the lanthanum-containing strontium titanate particles to approach a spherical shape, and the easier it is for the lanthanum-containing strontium titanate particles to be fixed in the recesses on the surface of the toner base particles. However, if the amount of lanthanum doped is too large, the dielectric constant of the toner increases, the loss dielectric constant increases, and the responsiveness to the development electric field may decrease. On the other hand, if the amount of lanthanum is 12% by mass or less, the developability is good even when continuous printing is performed at a high image density.

[0078] The amount of lanthanum in the lanthanum-containing strontium titanate particles can be measured using a scanning X-ray fluorescence analyzer (e.g., ZSX Primus IV, manufactured by Rigaku Corporation). As a specific measurement method, 2 g of the sample is filled into a tablet molding ring with a diameter of 20 mm, and pressed into pellets. Then, the measurement is performed under the following conditions. X-ray generating unit conditions: target Rh, tube voltage 50 kV Spectroscopic system conditions: Slit S2, spectroscopic crystal LiF, detector SC

[0079] On the other hand, a number of samples with different ratios of lanthanum titanate and strontium titanate are prepared and similarly measured using the scanning X-ray fluorescence analyzer to create a calibration curve. When creating the calibration curve, the ratio of lanthanum is calculated from the following formula. Ratio of lanthanum [mass%] = lanthanum [mass%] / (lanthanum [mass%] + strontium [mass%] The calibration curve is then compared with the above-mentioned measured values ​​to determine the amount of lanthanum.

[0080] The number average primary particle size of the lanthanum-containing strontium titanate particles is preferably 8 nm to 40 nm, more preferably 10 nm to 30 nm. When the number average primary particle size of the lanthanum-containing strontium titanate particles is within this range, as described above, the particles easily penetrate into the irregularities on the surface of the toner base particle, and easily adhere to the surface of the toner base particle.

[0081] The number average primary particle size of the lanthanum-containing strontium titanate particles can be specified by observation with a scanning electron microscope (hereinafter also referred to as "SEM"). Specifically, an SEM photograph of the toner is taken by an SEM (e.g., JEM-7401F, manufactured by JEOL Ltd., etc.) at a magnification of 30,000 times. The SEM photograph is then observed to measure the particle size (Ferret diameter) of the primary particles of the lanthanum-containing strontium titanate particles. The particle size measurement is performed by selecting an area in the SEM image where the total number of particles is about 100 to 200. The particle sizes (Ferret diameters) of 100 particles are then measured, and the average value is taken as the number average primary particle size.

[0082] The lanthanum-containing strontium titanate particles may be surface-treated with a coupling agent. When the lanthanum-containing strontium titanate particles are surface-treated with a coupling agent, the adhesion of the lanthanum-containing strontium titanate particles to the toner base particles and the cohesion of the lanthanum-containing strontium titanate particles with each other are adjusted. In addition, the lanthanum-containing strontium titanate particles treated with a coupling agent are easily fixed to the recesses of the toner base particles.

[0083] The type of coupling agent is not particularly limited, and examples thereof include alkylsilazane compounds such as hexamethyldisilazane; alkylalkoxysilane compounds such as dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, methyltrimethoxysilane, and butyltrimethoxysilane; chlorosilane compounds such as dimethyldichlorosilane and trimethylchlorosilane; silicone oil; silicone varnish; and coupling agents represented by the following general formula (1): XM(OR)3(1) In the above general formula (1), M represents titanium or silicon, and is preferably silicon, and X represents an alkyl group having 4 to 12 carbon atoms, and each R independently represents a methyl group or an ethyl group.

[0084] The coupling agent can be used alone or in combination of two or more. Among the above, the silane coupling agent or titanium coupling agent represented by the general formula (1) is particularly preferred. The silane coupling agent or titanium coupling agent having the above structure has high hydrophobicity because it contains an alkyl group in the structure. Therefore, water is less likely to be adsorbed to the toner particles (especially the lanthanum-containing strontium titanate particles), and the electrical properties of the lanthanum-containing strontium titanate particles are less likely to change.

[0085] Specific examples of the silane coupling agent represented by the above general formula (1) include isobutyltrimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, octyltriethoxysilane, and the like.

[0086] The method of treating the lanthanum-containing strontium titanate particles with a coupling agent is not particularly limited, but examples include spraying the coupling agent on the surface of the lanthanum-containing strontium titanate particles, or mixing the vaporized coupling agent with the lanthanum-containing strontium titanate particles and heat treating them. At this time, water, amines, and other catalysts may be used. The surface modification with the coupling agent is preferably carried out under an inert gas atmosphere such as nitrogen.

[0087] Alternatively, a method may be used in which a coupling agent, lanthanum-containing strontium titanate particles, and a solvent are mixed, and the mixture is heated and dried. In this case, either the coupling agent or the lanthanum-containing strontium titanate particles may be dispersed in the solvent first, or all of the components may be mixed at the same time.

[0088] Here, the amount of the coupling agent for treating the lanthanum-containing strontium titanate particles is preferably an amount that results in a carbon content of the lanthanum-containing strontium titanate particles of 1.0 to 8.0% by mass, and the carbon content is more preferably 2.0 to 7.0%. The carbon content of the lanthanum-containing strontium titanate particles is a characteristic value that correlates with the surface treatment amount. For example, when an alkylsilane coupling agent is used, the carbon content increases as the surface treatment amount increases. In addition, the carbon content increases when the number of carbon atoms in the alkyl group of the alkylsilane coupling agent is large. When the carbon content is within the above range, the lanthanum-containing strontium titanate particles have appropriate hydrophobicity, and not only are the electrical properties less likely to change, but also the particles are more likely to adhere to the toner base particles.

[0089] The carbon content of lanthanum-containing strontium titanate particles can be determined by burning the lanthanum-containing strontium titanate particles under an oxygen stream and measuring the absorbance of the generated CO and CO2 with an infrared spectrophotometer (IR). Specifically, a ceramic crucible is placed on the balance of a commercially available carbon analyzer (e.g., IR-212, manufactured by LECO), and 1 g of the measurement sample (lanthanum-containing strontium titanate particles) is placed in the crucible. In addition, a spatula's worth of a combustion improver is added. Then, a combustion process is performed using oxygen as the combustion gas, and the amount of carbon in the lanthanum-containing strontium titanate particles is measured.

[0090] Here, the amount of the lanthanum-containing strontium titanate particles in the toner particles is preferably 0.05 to 2.0% by mass, more preferably 0.1 to 1.0% by mass, based on the amount of the toner base particles. When the amount of the lanthanum-containing strontium titanate particles is 0.05% by mass or more, the recesses of the toner base particles are easily filled with the lanthanum-containing strontium titanate particles, and the charging characteristics of the toner tend to be uniform. On the other hand, when the amount of the lanthanum-containing strontium titanate particles is 2.0% by mass or less, the lanthanum-containing strontium titanate particles are less likely to aggregate, and good charging characteristics tend to be obtained.

[0091] (Other particles) In addition to the lanthanum-containing strontium titanate particles, the external additive may contain other particles to control the fluidity and charging characteristics of the toner particles. Examples of the other particles include silica particles, titania particles, alumina particles, zirconia particles, zinc oxide particles, chromium oxide particles, cerium oxide particles, antimony oxide particles, tungsten oxide particles, tin oxide particles, tellurium oxide particles, manganese oxide particles, and boron oxide particles. The number-average primary particle size of the other particles can be adjusted, for example, by classification or mixing classified products.

[0092] Other particles may be hydrophobized with a known surface modifier. Examples of the surface modifier include silane coupling agents, titanate coupling agents, aluminate coupling agents, fatty acids, metal salts of fatty acids or esters thereof, rosin acid, silicone oil, etc.

[0093] The amount of the other particles is preferably 0.05 to 2.0% by mass, and more preferably 0.1 to 1.0% by mass, based on the amount of the toner base particles.

[0094] (3) Physical properties of toner particles The size and shape of the toner particles including the toner base particles and the external additives are not particularly limited as long as they do not impair the effects and objects of the present invention. Usually, the volume-based median diameter (D50) of the toner particles is preferably 4.5 μm or more and 8.0 μm or less, and the average circularity of the toner particles is preferably 0.920 or more and 1.000 or less. The method for measuring the volume-based median diameter (D50) of the toner particles and the average circularity of the toner particles are the same as the method for measuring the volume-average particle diameter of the toner base particles and the method for measuring the average circularity of the toner particles.

[0095] In the toner containing the above toner particles, the adhesion strength of the lanthanum-containing strontium titanate particles on the toner particle surface, calculated by the following formula (A), is preferably within a range of 45 to 85%, and more preferably 50% or more and 80% or less. Adhesion strength of lanthanum-containing strontium titanate particles = (abundance ratio of Sr atoms in toner after ultrasonic treatment / abundance ratio of Sr atoms in toner before ultrasonic treatment) x 100 Formula (A)

[0096] In the above formula (A), the toner after ultrasonic treatment refers to a toner (toner particles) obtained by wetting 3 g of toner (or toner particles) with 40 g of a 0.2% by mass aqueous solution of polyoxyethyl phenyl ether in a 100 mL plastic cup, applying ultrasonic energy at a current value of 60 μA for 3 minutes using an ultrasonic homogenizer, filtering using a filter with an opening of 1 μm, washing with 60 mL of pure water, and drying. Examples of ultrasonic homogenizers include US-1200, manufactured by Nippon Kikai Co., Ltd., etc. As described later, a two-component developer contains toner particles and carrier particles. In this case, the ultrasonic treatment may be performed on the toner in the state where the carrier particles are present, or the carrier particles may be removed from the toner to leave only the toner particles, and then the ultrasonic treatment may be performed. The toner before ultrasonic treatment refers to a toner in a state where the ultrasonic treatment has not been performed.

[0097] The Sr atom abundance ratio in formula (A) refers to a value calculated based on the following formula (B) from the peak areas of individual atoms obtained by measuring the surface of the toner particles by X-ray electron spectroscopy. 元素 represents the peak area of ​​the subscripted element. Sr atom abundance ratio = (peak area Sr / (peak area C +Peak Area O +Peak Area Si +Peak Area Ti +Peak Area Sr ))×100 atom%...Formula (B)

[0098] A more specific method for determining the above Sr atom abundance ratio is described below. First, the peak area (peak area Sr ), the peak area of ​​carbon element (peak area Y C ), the peak area of ​​oxygen element (peak area O ), silicon peak area (peak area Si), and the peak area of ​​titanium element (peak area Ti ) is identified. Each peak area is identified using a relative sensitivity factor from each atomic peak area. Then, from each peak area thus obtained, the abundance ratio of Sr atoms is calculated based on the above formula (B). (Measurement conditions) X-ray: Al monochromatic source Acceleration: 12kV, 6mA Resolution: 50eV Beam system: 400μm Pass energy: 50 eV Step size: 0.1 eV

[0099] Here, when determining the adhesive strength of the lanthanum-containing strontium titanate particles, X-ray photoelectron spectroscopy is performed before and after the ultrasonic treatment to determine the abundance ratio of Sr atoms, and the ratio of the abundance ratio of Sr atoms before and after the ultrasonic treatment is determined.

[0100] The ratio of the Sr atom abundance ratio before and after ultrasonic treatment represents the adhesion strength of the lanthanum-containing strontium titanate particles in the toner particles. That is, it represents the strength with which the lanthanum-containing strontium titanate particles are fixed to the toner base particles. Here, when the adhesion strength is less than 45%, even if the lanthanum-containing strontium titanate particles are attached to the toner base particles, they are unlikely to stay in one place and may not contribute to the uniformity of the charging characteristics. On the other hand, when the adhesion strength is more than 85%, many of the lanthanum-containing strontium titanate particles may be buried in the toner base particles, and the effect of adding the lanthanum-containing strontium titanate particles (improving the fluidity of the toner particles, uniformizing the charging characteristics, etc.) may not be sufficiently obtained. On the other hand, when the adhesion strength is 45% or more and 85% or less, the lanthanum-containing strontium titanate particles are attached to the toner base particles with a moderate strength, and the fluidity of the toner particles is improved and the charging characteristics are likely to be uniform.

[0101] (4) Method of manufacturing toner particles The method for producing the toner particles is not particularly limited, and the toner particles can be produced by a known method. For example, the toner particles may be prepared by the above-described method for preparing the toner particles, and an external additive may be attached to the surface of the toner particles.

[0102] The method for attaching the external additive to the surface of the toner base particles may be any method that can sufficiently mix the toner base particles and the external additive, and may be a method using a known mixing device such as a Turbula mixer, a Henschel mixer, a Nauta mixer, or a V-type mixer.

[0103] The obtained toner particles may be used as a toner (one-component developer) as it is, but it is preferable to mix the toner particles with carrier particles as described below and use the resulting toner particles as a two-component developer.

[0104] (5) Two-component developer The two-component developer can be prepared by mixing the above-mentioned toner particles with carrier particles and the like.

[0105] The carrier particles contained in the two-component developer may be conventionally known magnetic particles. Examples of the carrier particles include particles containing metals such as iron, ferrite, and magnetite, and alloys of these metals with metals such as aluminum and lead. The ferrite may be a ferrite containing a heavy metal such as copper, zinc, nickel, or manganese, or a light metal ferrite containing an alkali metal and / or an alkaline earth metal.

[0106] The carrier particles may be coated carrier particles having a core particle made of a magnetic material and a coating layer that coats the surface of the core particle. Furthermore, the carrier particles may be resin-dispersed carrier particles having fine powder of a magnetic material dispersed in a resin. Among these, coated carrier particles are particularly preferred.

[0107] Examples of the core material of the coated carrier particles include metal particles such as iron powder, ferrite, magnetite, etc., and particles in which these metals are dispersed in resin, and magnetite particles or ferrite particles are preferred. It is also preferred that the core particles of the carrier particles contain strontium. When the core particles contain strontium, the surface of the core particles becomes uneven, and even if the core particles are coated with a coating layer, a part of the core particles is exposed on the surface. As a result, the resistance of the carrier particles is adjusted to a desired range.

[0108] Examples of resins constituting the coating layer of the coated carrier particles include polyolefin resins such as polyethylene, polypropylene, chlorinated polyethylene, and chlorosulfonated polyethylene; polystyrene, polyacrylates such as polymethyl methacrylate, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinylidene resins such as polyvinyl chloride-vinyl acetate copolymer and styrene-acrylic acid copolymer; silicone resins consisting of organosiloxane bonds or modified resins thereof (for example, modified resins made of alkyd resin, polyester resin, epoxy resin, polyurethane, etc.); fluororesins such as polytetrachloroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyamide; polyester; polyurethane; polycarbonate; amino resins such as urea-formaldehyde resin; and epoxy resins.

[0109] Among these, polyacrylate resins are preferred, more preferably those containing a structure derived from an alicyclic (meth)acrylic acid ester compound, and even more preferably a copolymer of an alicyclic (meth)acrylic acid ester compound and methyl methacrylate. When the coating layer contains the resin, the hydrophobicity of the coating layer increases, and the amount of water adsorbed by the carrier particles decreases, particularly under high temperature and high humidity. Therefore, the decrease in the charge amount of the carrier under high temperature and high humidity is easily suppressed. In addition, since the structure derived from an alicyclic (meth)acrylic acid ester has a rigid cyclic skeleton, the strength of the coating layer increases, and the durability of the carrier improves.

[0110] The coated carrier particles can be prepared by a known method, such as a wet coating method or a dry coating method.

[0111] Here, the resistance of the carrier particles is 1.0×10 9 ~1.0×10 11 Ω cm is preferred, 1.0×10 9 ~5.0×10 10 Ω·cm is more preferable. When the resistance of the carrier particles is within the above range, the charge in the toner is less likely to leak, and the charge rises well in the developing device. The resistance of the carrier particles refers to the initial resistance of the carrier particles, and refers to the resistance of the carrier particles alone. The resistance is measured dynamically under development conditions using a magnetic brush. Specifically, an aluminum electrode drum of the same dimensions as the photosensitive drum is substituted for the photosensitive drum, carrier particles are supplied onto the developing sleeve to form a magnetic brush, this magnetic brush is rubbed against the electrode drum, and a voltage (500V) is applied between the sleeve and the drum to measure the current flowing between them. The resistance DVR of the carrier particles is then calculated from the following formula. DVR(ΩCM)=(V / I)×(N×L / Dsd) V: Voltage between the developing sleeve and drum (V) I: Measured current value (A) N: Development nip width (cm) L: Developing sleeve length (cm) DSD: Distance between developing sleeve and drum (cm) In this specification, the conditions for measuring the resistance DVR of the carrier particles are V=500 V, N=1 cm, L=6 cm, and Dsd=0.6 mm.

[0112] The average particle size of the carrier particles is preferably 10 μm to 100 μm, more preferably 20 μm to 80 μm, in terms of volume-based median diameter. The volume-based median diameter of the carrier particles can be measured, for example, by a laser diffraction particle size distribution analyzer (HELOS; SYMPATEC) equipped with a wet disperser.

[0113] The carrier particles may be mixed in an appropriate amount with the toner particles. Examples of the mixing device used for the mixing include a Nauta mixer, a W-cone mixer, and a V-type mixer.

[0114] The ratio of toner particles to the total of carrier particles and toner particles in the two-component developer (toner concentration) is preferably 4.0 to 8.0% by mass. When the ratio of toner particles is 4.0 to 8.0% by mass, the toner has an appropriate charge amount, and the image quality at the initial stage and after continuous printing is improved. EXAMPLES

[0115] Specific examples of the present invention will be described below together with comparative examples, but the present invention is not limited thereto. In the examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.

[0116] A. Preparation of toner base particles A-1. Preparation of metal pigment dispersion The following materials were prepared: Aluminum pigment (2173EA manufactured by Showa Aluminum Powder Co., Ltd.): 100 parts by weight Anionic surfactant (Neogen R manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 1.5 parts by weight Ion-exchanged water: 900 parts by weight After removing the solvent from the aluminum pigment paste, all the materials were mixed and dispersed for 1 hour using an emulsifying disperser Cavitron (CR1010 manufactured by Pacific Machinery Co., Ltd.) to obtain a metal pigment dispersion (solid content: 10% by mass) in which the metal pigment (aluminum pigment) was dispersed.

[0117] A-2. Preparation of amorphous resin particle dispersion (1) First stage polymerization A monomer mixture 1 containing the following materials was prepared. Styrene: 584 parts by weight n-Butyl acrylate: 160 parts by weight Methacrylic acid: 56 parts by weight

[0118] Meanwhile, 4 parts by mass of sodium polyoxyethylene (2) dodecyl ether sulfate and 3000 parts by mass of ion-exchanged water were charged into a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introduction device. Then, the internal temperature was raised to 80°C while stirring at a stirring speed of 230 rpm under a nitrogen stream. After the temperature was raised, a solution of 10 parts by mass of potassium persulfate in 200 parts by mass of ion-exchanged water was added, and the liquid temperature was adjusted to 75°C. Then, the monomer mixture 1 was added dropwise over 1 hour. After the dropwise addition, polymerization was carried out while stirring at 75°C for 2 hours, to obtain a resin microparticle dispersion a.

[0119] (2) Second stage polymerization A monomer mixture 2 containing the following materials was prepared. Styrene: 239 parts by weight n-Butyl acrylate: 111 parts by weight Methacrylic acid: 26 parts by weight n-Octyl mercaptan: 3 parts by mass

[0120] Meanwhile, a solution of 2 parts by mass of sodium polyoxyethylene (2) dodecyl ether sulfate dissolved in 3000 parts by mass of ion-exchanged water was charged into a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introduction device, and heated to 80°C. Separately, a solution was prepared by dissolving or dispersing 42 parts by mass (solid content equivalent) of the above-mentioned resin microparticle dispersion liquid a and 70 parts by mass of microcrystalline wax HNP-0190 (manufactured by Nippon Seiro Co., Ltd.) in monomer mixture liquid 2 at 80°C. The solution was then added to the reaction vessel, and mixed and dispersed for 1 hour using a mechanical disperser CLEARMIX (manufactured by M-Technique Co., Ltd.) with a circulation path to obtain a dispersion containing emulsified particles (oil droplets).

[0121] Further, an initiator solution in which 5 parts by mass of potassium persulfate was dissolved in 100 parts by mass of ion-exchanged water was added to the dispersion, and polymerization was carried out with stirring at 80° C. for 1 hour to obtain a resin fine particle dispersion b.

[0122] (3) Third stage polymerization A monomer mixture 3 containing the following materials was prepared. Styrene: 380 parts by weight n-Butyl acrylate: 132 parts by weight Methacrylic acid: 39 parts by weight n-Octyl mercaptan: 6 parts by mass

[0123] A solution in which 10 parts by mass of potassium persulfate was dissolved in 200 parts by mass of ion-exchanged water was added to the above-mentioned resin particle dispersion liquid b. The above-mentioned monomer mixture liquid 3 was added dropwise to the solution over 1 hour at a temperature condition of 80°C. After the completion of the dropwise addition, the mixture was heated and stirred for 2 hours to carry out polymerization. Thereafter, the mixture was cooled to 28°C to obtain an amorphous resin particle dispersion liquid.

[0124] A-3. Preparation of crystalline resin particle dispersion (1) Preparation of crystalline resin 220 parts by mass of sebacic acid (molecular weight 202.25) and 298 parts by mass of 1,12-dodecanediol (molecular weight 202.33) were placed in a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and heated to 160°C to dissolve. Then, 2.5 parts by mass of tin(II) 2-ethylhexanoate and 0.2 parts by mass of gallic acid were added, and the mixture was heated to 210°C and reacted for 8 hours. The reaction was further continued for 1 hour at 8.3 kPa to obtain a crystalline resin.

[0125] A DSC curve was obtained for the obtained crystalline resin using a differential scanning calorimeter Diamond DSC (PerkinElmer) at a heating rate of 10°C / min. The melting point (Tm) measured by a method of measuring the endothermic peak top temperature was 82.8°C. In addition, the molecular weight was measured using gel permeation chromatography HLC-8120GPC (Tosoh Corporation), and the weight average molecular weight in terms of standard styrene was 28,000.

[0126] (2) Preparation of crystalline resin particle dispersion 100 parts by mass of the crystalline resin was dissolved in 400 parts by mass of ethyl acetate. Then, 25 parts by mass of a 5.0% by mass aqueous sodium hydroxide solution was added to prepare a resin solution. This resin solution was put into a container having a stirring device, and while stirring the resin solution, 638 parts by mass of a 0.26% by mass aqueous sodium lauryl sulfate solution was added dropwise over 30 minutes. During the drop of the aqueous sodium lauryl sulfate solution, the liquid in the reaction vessel became cloudy, and when the entire amount of the aqueous sodium lauryl sulfate solution was further added dropwise, an emulsion in which the crystalline resin particles were uniformly dispersed was prepared. Next, the emulsion was heated to 40°C, and ethyl acetate was distilled off under a reduced pressure of 150 hPa using a diaphragm vacuum pump V-700 (manufactured by BUCHI), to obtain a crystalline resin particle dispersion in which the crystalline polyester resin was dispersed.

[0127] A-4. Preparation of toner base particles (1) Agglomeration / fusion process A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introduction device was charged with 300 parts by mass (solid content equivalent) of amorphous resin particle dispersion, 60 parts by mass (solid content equivalent) of crystalline resin particle dispersion, 1100 parts by mass of ion-exchanged water, and 40 parts by mass of metal pigment dispersion (solid content equivalent), and the liquid temperature was adjusted to 30°C. Then, a 5N aqueous sodium hydroxide solution was added to adjust the pH to 10. Next, an aqueous solution in which 60 parts by mass of magnesium chloride was dissolved in 60 parts by mass of ion-exchanged water was added at 30°C over 10 minutes under stirring. After holding for 3 minutes, the temperature was raised, and the system was heated to 85°C over 60 minutes and held at 85°C to continue the particle growth reaction. The particle size of the aggregated particles was measured using a Coulter Multisizer 3 (manufactured by Beckman Coulter, Inc.). When the volume-based median diameter reached 6.2 μm, an aqueous solution of 40 parts by mass of sodium chloride dissolved in 160 parts by mass of ion-exchanged water was added to stop particle growth. Furthermore, as a maturation process, the mixture was heated and stirred at a liquid temperature of 80°C for one hour to promote fusion between the particles, thereby preparing a dispersion of toner base particles with a circularity of 0.97.

[0128] (2) Washing and drying process The resulting dispersion of toner base particles was subjected to solid-liquid separation using a basket centrifuge (MARKIII Model No. 60×40+M, manufactured by Matsumoto Kikai Co., Ltd.) to form a wet cake of toner base particles. This wet cake was washed with ion-exchanged water at 40° C. until the electrical conductivity of the filtrate from the basket centrifuge reached 5 μS / cm, and then transferred to a flash jet dryer (manufactured by Seishin Enterprise Co., Ltd.) and dried until the moisture content reached 0.5% by mass to obtain toner base particles.

[0129] B. Preparation of lanthanum-containing strontium titanate particles B-1. Preparation of surface-treated lanthanum-containing strontium titanate particles 1 (1) Preparation of lanthanum-containing strontium titanate particles 1 Metatitanic acid obtained by the sulfuric acid method was bleached to remove iron, and then desulfurized by adding an aqueous solution of sodium hydroxide to adjust the pH to 9.0. The mixture was then neutralized to pH 5.8 with hydrochloric acid, filtered, and washed with water. Water was added to the washed cake to make a slurry with a TiO2 content of 1.85 mol / L. Hydrochloric acid was then added to adjust the pH to 1.0 and peptized. After the treatment, metatitanic acid with a TiO2 content of 0.625 mol was collected and placed in a 3L reaction vessel. Furthermore, a total of 0.719 mol of an aqueous solution of strontium chloride, lanthanum chloride, and barium chloride was added so that the molar ratio of SrO / LaО / TiO2 was 1.00 / 0.08 / 1.00. The TiO2 concentration was then adjusted to 0.313 mol / L. The mixture was then heated to 90°C while stirring and mixing. Then, 296 mL of a 5N aqueous sodium hydroxide solution was added over 12 hours, and the mixture was then stirred at 95° C. for 1 hour to complete the reaction.

[0130] The reaction slurry was cooled to 50°C, hydrochloric acid was added until the pH reached 5.0, and stirring was continued for 1 hour. The resulting precipitate was washed by decantation, and hydrochloric acid was added to the slurry containing the precipitate to adjust the pH to 6.5. Then, 9% by mass of isobutyltrimethoxysilane based on the solid content was added and stirred for 1 hour. Next, filtration and washing were performed, and the resulting cake was dried in the air at 120°C for 8 hours to obtain lanthanum-containing strontium titanate particles 1. The resulting particles were observed with a transmission electron microscope, and the number average primary particle size was calculated based on weight to be 20 nm.

[0131] (2) Surface treatment The lanthanum-containing strontium titanate particles 1 obtained above were placed in a reaction vessel. Under a nitrogen atmosphere, 20 g of a hydrophobic treatment agent, isobutyltrimethoxysilane, diluted with 60 g of hexane, was added per 100 g of powder while stirring the powder with a rotating blade. The mixture was heated to 200°C and stirred for 120 minutes, and then cooled with cooling water to obtain surface-treated lanthanum-containing strontium titanate particles 1. The carbon content was measured by the method described below.

[0132] B-2. Preparation of surface-treated lanthanum-containing strontium titanate particles 2-4 and 15 Except for changing the time for adding sodium hydroxide during the production of lanthanum-containing strontium titanate particles 1, the particles were prepared in the same manner as lanthanum-containing strontium titanate particles 1. As a result, as shown in Table 1, the particle size and surface treatment amount (carbon content) of the lanthanum-containing strontium titanate particles were changed.

[0133] B-3. ​​Preparation of surface-treated lanthanum-containing strontium titanate particles 5-7 Lanthanum-containing strontium titanate particles were prepared in the same manner as lanthanum-containing strontium titanate particles 1, except that the SrO / LaО / TiO2 molar ratio was changed. As a result, the lanthanum content of the lanthanum-containing strontium titanate particles was changed, as shown in Table 1.

[0134] B-4. Preparation of surface-treated lanthanum-containing strontium titanate particles 8-12 and 14 The particles were prepared in the same manner as above, except that the silane coupling agent used in the surface treatment of the lanthanum-containing strontium titanate particles 1 was changed to octyltriethoxysilane (C8), decyltrimethoxysilane (C10), hexamethyldisilazane (HMDS), polydimethylsiloxane (PMDS), none, or pentyltrimethoxysilane (C5), as shown in Table 1. This resulted in a change in the amount of surface treatment (carbon content) of the lanthanum-containing strontium titanate particles.

[0135] B-5. Preparation of surface-treated lanthanum-containing strontium titanate particles 13 The same preparation as above was carried out except that the stirring time during the surface treatment of the lanthanum-containing strontium titanate particles 1 was changed, thereby changing the surface treatment amount (carbon content) of the lanthanum-containing strontium titanate particles.

[0136] B-6. Preparation of surface-treated lanthanum-free strontium titanate particles 16 Lanthanum-containing strontium titanate particles 1 were prepared in the same manner as lanthanum-containing strontium titanate particles 1, except that lanthanum chloride was not added.

[0137] B-7.Method for measuring carbon content in lanthanum-containing strontium titanate particles Lanthanum-containing strontium titanate particles were burned under an oxygen stream, and the absorbance of the generated CO and CO2 was measured by an infrared spectrophotometer (IR). Specifically, a ceramic crucible was placed on the balance of a commercially available carbon analyzer (IR-212, manufactured by LECO Co. Ltd.), and 1 g of the measurement sample was weighed into the crucible. After weighing the measurement sample, one spatula's worth of combustion improver was added. Then, the measurement sample and the crucible containing the combustion improver were placed on the ceramic stand of the device, and a combustion process was performed using oxygen as the combustion gas, and the carbon amount was measured.

[0138] C. Preparation of Toner Particles C-1. Preparation of Toner Particle 1 (Example 1) 100 parts by mass of the above-mentioned toner base particles, 1.0 part by mass of silica particles 1 (HMDS treatment, number average primary particle size = 20 nm), 0.4 part by mass of silica particles 2 (HMDS treatment, number average primary particle size = 8 nm), and 0.5 parts by mass of lanthanum-containing strontium titanate particles 1 were mixed and placed in a Henschel mixer, model FM20C / I (manufactured by Nippon Coke & Engineering Co., Ltd.). The rotation speed was set so that the blade tip peripheral speed was 50 m / s, and the mixture was stirred for 20 minutes to prepare toner particles 1 containing the toner base particles and lanthanum-containing strontium titanate particles 1. The temperature during mixing of the lanthanum-containing strontium titanate particles was 40°C ± 1°C, and when it reached 41°C, cooling water was flowed into the outer bath of the Henschel mixer at a flow rate of 5 L / min. On the other hand, when it reached 39°C, cooling water was flowed at a flow rate of 1 L / min to control the temperature inside the Henschel mixer. The adhesion strength of the lanthanum-containing strontium titanate particles in the obtained toner particles was measured by the method described below.

[0139] C-2. Preparation of Toner Particles 2 to 25 (Examples 2 to 25 and Comparative Examples 1 and 2) Toner particles were prepared in the same manner as toner particles 1, except that the type or amount of lanthanum-containing strontium titanate particles was changed as shown in Table 1.

[0140] C-3. Adhesion strength of lanthanum-containing strontium titanate particles (Determining the strontium surface ratio (atom%) of toner (toner particles) before ultrasonic treatment) For each of the toner particles, the peak area (peak area Sr ), carbon element peak area (peak area C ), the peak area of ​​oxygen element (peak area O ), silicon peak area (peak area Si ), and the peak area of ​​titanium element (peak area TiThe peak area of ​​each element was determined using the relative sensitivity factor from each atomic peak area. (Measurement conditions) X-ray: Al monochromatic source Acceleration: 12kV, 6mA Resolution: 50eV Beam system: 400μm Pass energy: 50 eV Step size: 0.1 eV

[0141] From the obtained element concentrations, the Sr atom abundance ratio in the toner particles before the ultrasonic treatment was calculated based on the following formula (B). Sr atom abundance ratio = (peak area Sr / (peak area C +Peak Area O +Peak Area Si +Peak Area Ti +Peak Area Sr ))×100 atom%...Formula (B))

[0142] (Determining the strontium surface ratio (atom%) of toner (toner particles) after ultrasonic treatment) Next, the following ultrasonic treatment was performed. First, 3 g of toner particles were placed in a 100 ml plastic cup and moistened with 40 g of a 0.2 mass % aqueous solution of polyoxyethyl phenyl ether. Then, using an ultrasonic homogenizer (US-1200, manufactured by Nippon Kikai Co., Ltd.), the ultrasonic energy was adjusted so that the value of the ammeter attached to the main device indicated 60 μA, and ultrasonic treatment was performed for 3 minutes. After that, the toner particles were filtered using a filter with a mesh size of 1 μm, washed with 60 ml of pure water, and dried.

[0143] Thereafter, similarly to the above, X-ray photoelectron spectroscopy was performed to determine the strontium surface ratio of the toner particles after the ultrasonic treatment, and the adhesion strength of the lanthanum-containing strontium titanate particles was calculated based on the following formula (A). Adhesion strength of lanthanum-containing strontium titanate particles = (abundance ratio of Sr atoms in toner particles after ultrasonic treatment / abundance ratio of Sr atoms in toner particles before ultrasonic treatment) x 100 Formula (A) The obtained values ​​are shown in Table 1. The value is passed when it is between 45% and 85%.

[0144] C-5. Preparation of Colored Toner (Toner Particles 26) (Reference Example) Toner particles 26 were prepared in the same manner as the above-mentioned toner particles 1, except that the following colored particle dispersion was used instead of the metal pigment dispersion when preparing the toner base particles.

[0145] (Preparation of Colorant Particle Dispersion) 90 parts by mass of sodium dodecyl sulfate was dissolved in 1600 parts by mass of ion-exchanged water by stirring. While stirring this solution, 420 parts by mass of colorant particles (carbon black Regal 330R, manufactured by Cabot Corporation) were gradually added. Next, a dispersion liquid of colorant particles was prepared by dispersing using a stirring device Clearmix (manufactured by M Technique Co., Ltd.). The particle size of the colorant particles in the dispersion liquid was measured using a particle size distribution measuring device "Nanotrack Wave" (manufactured by Microtrack Bell Co., Ltd.) and was found to be 117 nm.

[0146] D. Preparation of Two-Component Developer D-1. Preparation of carrier particles (1) Preparation of carrier core particles Each component was weighed out in the following ratio: MnO 35 mol%, MgO 14.5 mol%, Fe2O3 50 mol%, and SrO 0.5 mol%. The mixture was mixed with water and ground in a wet media mill for 5 hours to obtain a slurry. The obtained slurry was dried in a spray dryer to obtain spherical particles. The particles were adjusted in particle size, then heated at 950°C for 2 hours and pre-fired. The particles were ground in a wet ball mill for 1 hour using stainless steel beads with a diameter of 0.3 cm. The particles were then further ground for 4 hours using zirconia beads with a diameter of 0.5 cm.

[0147] Polyvinyl alcohol (PVA) was added as a binder at 0.8% by mass relative to the solid content, then granulated and dried using a spray dryer, and then sintered in an electric furnace at 1350°C for 5 hours. The mixture was then crushed, classified to adjust the particle size, and magnetic separation was used to separate out low magnetic particles to obtain carrier core particles. The particle size of the carrier core particles was 35 μm.

[0148] (2) Preparation of materials for the coating layer Cyclohexyl methacrylate and methyl methacrylate were added to an aqueous solution of 0.3% by mass of sodium benzenesulfonate in a mass ratio (copolymerization ratio) of 5:5, and potassium persulfate was added in an amount equivalent to 0.5% by mass of the total amount of monomers to carry out emulsion polymerization. The polymer was dried by spray drying to prepare a material for the coating layer. The weight average molecular weight of the obtained material for the coating layer was 500,000.

[0149] (3) Preparation of carrier particles 100 parts by mass of the carrier core particles and 4.5 parts by mass of the coating layer material were put into a high-speed stirring mixer equipped with horizontal stirring blades, and mixed and stirred for 15 minutes at 22° C. under conditions of a horizontal rotor peripheral speed of 8 m / sec. Thereafter, the mixture was mixed for 50 minutes at 120° C. to form a coating layer on the surface of the core particles by the action of mechanical impact force (mechanochemical method), thereby preparing carrier particles.

[0150] D-2. Preparation of two-component developer (1) Preparation of Two-Component Developer 1 The toner particles 1 and carrier particles prepared as above were mixed so that the toner particle concentration became 6.5% by mass to prepare a two-component developer 1. The mixing was carried out for 30 minutes using a V-type mixer.

[0151] (2) Preparation of two-component developers 2 to 26 Two-component developers 2 to 23 were prepared in the same manner as two-component developer 1, except that toner particles 1 were changed to toner particles 2 to 26.

[0152] E. Evaluation The amount of toner scattering was evaluated for each of the two-component developers (toners) described above as follows. The results are shown in Table 1.

[0153] [Evaluation of toner scattering amount] The amount of scattered toner was measured using a particle counter (KR-12A, manufactured by RION) as follows. The developing unit containing the two-component developer was set on a drive unit capable of rotating the developing roller, and the suction port of the particle counter was set at a position 1 cm away from the front end of the developing roller. The particle size measurement range of the particle counter was set to 2 to 10 μm, and the developing roller was rotated at 270 rpm. The measurement with the particle counter was repeated five times, with a 20-second count and a 10-second stop, and the average of the five measurements was taken as the amount of scattered toner.

[0154] The above scattering amount measurement was carried out three times, after filling the developer with two-component developer and stirring for one minute (initial stage), mounting the developer on a commercially available electrophotographic image forming device bizhub C368 (manufactured by Konica Minolta), and printing 50,000 sheets of horizontal bands with a print area ratio of 5% under an environment of 23°C and 50% RH (endurance NN environment), and after printing 50,000 sheets of horizontal bands with a print area ratio of 5% under an environment of 30°C and 80% RH (endurance HH environment), and was evaluated under the following conditions. Of the following evaluations, ◎ and ○ were considered to be acceptable. ◎: The amount of toner scattering is less than 20,000 particles / L ○: The amount of toner scattering is more than 20,000 particles / L and less than 50,000 particles / L. ×: The amount of toner scattering is more than 50,000 particles / L

[0155] [Table 1]

[0156] As shown in Table 1 above, in the toner containing the toner base particles and the lanthanum-containing strontium titanate particles, the amount of toner scattering was small in the initial stage, the NN durability environment, and the HH durability environment (Examples 1 to 23). In contrast, in the case of a combination of the toner base particles and the lanthanum-free strontium titanate particles, the initial scattering amount was small, but the scattering amount after printing was large (Comparative Example 1). It is presumed that it was difficult to sufficiently uniformize the charging characteristics of the toner surface.

[0157] On the other hand, when strontium titanate particles were not included, the amount of toner scattering was large from the beginning (Comparative Example 2).

[0158] Furthermore, when the lanthanum-containing strontium titanate particles were surface-treated with a silane coupling agent (Examples 1 to 18, 20, and 21), the initial scattering amount was smaller than when the particles were not surface-treated (Comparative Example 19). However, when the particle size of the strontium titanate particles was relatively large (Example 22) or the content of the strontium titanate particles was relatively high (Example 23), the scattering amount was likely to be large.

[0159] In the reference example that did not contain a metal pigment, the amount of scattering was not increased even though it did not contain strontium titanate. In other words, the problem of the present application is a problem that occurs when a metal pigment is contained. [Industrial Applicability]

[0160] The electrostatic image developing toner of the present invention can suppress toner scattering even during continuous printing, and is therefore useful in various printing fields.

Claims

1. toner base particles containing a binder resin and a metal pigment; an external additive containing lanthanum-containing strontium titanate particles; Including, At least a portion of the metal pigment is present on the surface of the toner base particle, The number average primary particle size of the lanthanum-containing strontium titanate particles is 8 to 40 nm. Toner for developing electrostatic images.

2. The toner base particles are obtained by aggregating and fusing the binder resin particles and the metal pigment. The toner for developing electrostatic images according to claim 1.

3. the amount of the lanthanum-containing strontium titanate particles is 0.05 to 2.0% by mass relative to the amount of the toner base particles; 3. The toner for developing electrostatic images according to claim 1 or 2.

4. The amount of lanthanum atoms in the lanthanum-containing strontium titanate particles is 3 to 12 mass%. The toner for developing electrostatic images according to any one of claims 1 to 3.

5. The lanthanum-containing strontium titanate particles are surface-treated with a coupling agent represented by the following general formula (1): The toner for developing electrostatic images according to any one of claims 1 to 4. X-M(OR) 3 (1) (In the general formula (1), M represents titanium or silicon; X represents an alkyl group having 4 to 12 carbon atoms; Each R independently represents a methyl group or an ethyl group.

6. The carbon content of the lanthanum-containing strontium titanate particles surface-treated with the coupling agent is 1.0 to 8.0 mass%. The toner for developing electrostatic images according to claim 5 .

7. the adhesion strength of the lanthanum-containing strontium titanate particles on the particle surface of the toner, which is represented by the following formula (A), is within a range of 45 to 85%; The toner for developing electrostatic images according to any one of claims 1 to 6. Adhesion strength of lanthanum-containing strontium titanate particles=(abundance ratio of Sr atoms in the toner for developing electrostatic images after ultrasonic treatment / abundance ratio of Sr atoms in the toner for developing electrostatic images before ultrasonic treatment)×100 (Equation (A)) (The toner for developing electrostatic images after ultrasonic treatment in formula (A) is the toner for developing electrostatic images obtained by wetting 3 g of the toner for developing electrostatic images with 40 g of a 0.2 mass % aqueous solution of polyoxyethyl phenyl ether in a 100 mL plastic cup, applying ultrasonic energy at a current value of 60 μA for 3 minutes using an ultrasonic homogenizer, filtering the toner using a filter having an opening of 1 μm, washing the toner with 60 mL of pure water, and drying the toner. The Sr atom abundance ratio in formula (A) is a value calculated based on the following formula (B) from the peak area of ​​each atom obtained by measuring the surface of the toner for developing electrostatic images by X-ray electron spectroscopy. Sr atom abundance ratio = (peak area Sr / (peak area C + Peak area O + Peak area Si + Peak area Ti + Peak area Sr ))×100 atom%...Formula (B))

Citation Information

Patent Citations

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, image forming method, and image forming apparatus

    JP2017062315A